2012
DOI: 10.4067/s0034-98872012000700015
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de ovario poliquístico y embarazo

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine metabolic dysfunction closely associated with insulin resistance and obesity, which predisposes to pregnancy complications and prenatal programming of the offspring. The aim of this review is to report our experience in PCOS patients, caracterizada por oligo-ovulación e hiperandrogenismo, lo que compromete la función reproductiva de la mujer. Su etiología es incierta y se encuentra en estrecha asociación a la resistencia insulínica (RI), la que juega un pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
6
0
5
Order By: Relevance
“…In the human, cotyledons protrude into the extended maternal intervillous blood space of the single polycotyledonary placental disc (Kaufmann et al 1985, Mossman 1987, Leiser 1991, Leiser & Kaufmann 1994, Leiser et al 1997, Parker & Douglas 2010). As such, findings from this study may have implications relative to placental development in pregnant women with elevated androgen levels, such as polycystic ovary syndrome (PCOS) (Sir-Petermann et al 2002, Sir-Petermann et al 2012) or congenital adrenal hyperplasia (CAH) (Lo & Grumbach 2001). It is of interest in this regard that female offspring of gestational T-treated sheep manifest reproductive and metabolic features of women with PCOS (Padmanabhan et al 2010, Padmanabhan & Veiga-Lopez 2011, Padmanabhan & Veiga-Lopez 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human, cotyledons protrude into the extended maternal intervillous blood space of the single polycotyledonary placental disc (Kaufmann et al 1985, Mossman 1987, Leiser 1991, Leiser & Kaufmann 1994, Leiser et al 1997, Parker & Douglas 2010). As such, findings from this study may have implications relative to placental development in pregnant women with elevated androgen levels, such as polycystic ovary syndrome (PCOS) (Sir-Petermann et al 2002, Sir-Petermann et al 2012) or congenital adrenal hyperplasia (CAH) (Lo & Grumbach 2001). It is of interest in this regard that female offspring of gestational T-treated sheep manifest reproductive and metabolic features of women with PCOS (Padmanabhan et al 2010, Padmanabhan & Veiga-Lopez 2011, Padmanabhan & Veiga-Lopez 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found placental alterations (Palomba et al 2013) and altered steroid production (Maliqueo et al 2013) in PCOS pregnancies. Interestingly, gestational diabetic mothers also have high levels of androgens (Sir-Petermann et al 2002, Sir-Petermann et al 2012). Placental morphology is also altered in diabetic pregnancies, with increased androgen levels (Higgins et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Findings that prenatal exposure to excess androgens leads to the development of a PCOS-like phenotype during adulthood in several animal models (discussed below) (Padmanabhan and Veiga-Lopez, 2013a, Padmanabhan and Veiga-Lopez, 2013b, Abbott et al, 1998) also substantiate this premise. A possibility to consider is that hyperandrogenism may be involved in the vertical transmission of PCOS in humans, as PCOS women exhibit increased levels of androgens during pregnancy (Sir-Petermann et al, 2002, Sir-Petermann et al, 2012). …”
Section: Development Of Pcosmentioning
confidence: 99%
“…In addition, these infants are more likely to be born by Caesarean section and have lower birth weight (Boomsma et al, 2006). Because women with PCOS are also likely to be hyperandrogenic during pregnancy (Sir-Petermann et al, 2002, Sir-Petermann et al, 2012), endocrine alterations during gestation (Sir-Petermann et al, 2007a) may contribute to increased risk for their female offspring to also develop PCOS. This premise is further supported by observations that hyperandrogenic maternal environment in patients with congenital adrenal hyperplasia (CAH) and gestational androgen treatment in experimental animal models can lead to development of PCOS phenotype in the female offspring (Abbott et al, 1998, Barnes et al, 1994, Padmanabhan and Veiga-Lopez, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Durante el embarazo se produce disminución de la secreción gonadotrópica por las hormonas placentarias y, la hipersecreción de la hormona luteinizante (LH de sus siglas en inglés) debe quedar eliminada, por lo que el embarazo puede tener un efecto beneficioso sobre el SOP. Sin embargo, dado que el embarazo es un estado fisiológico de resistencia insulínica, es probable que en las pacientes con SOP y RI, esto constituya un factor agravante de la resistencia a la insulina preexistente, desencadenando una DMG [69].…”
Section: Capítulo 3: Justificación Del Estudiounclassified